The TICKPRO computer program for predicting Ixodes ricinus host-seeking activity and the warning system published on websites - Daniel, Milan; Vráblík, Tomás; Valter, Jaroslav; Kríz, Bohumír; Danielová, Vlasta (Central European journal of public health, 2010)
The computer program with the acronym TICKPRO (tick prognosis) facilitates medium-range forecasts of the level of host-seeking activity in ticks within a 1-4 day horizon. The program is based on the medium-range weather forecast routinely produced at the Czech Hydrometeorological Institute (CHMI), as well as on previously developed mathematical models describing the correlation of meteorological factors with the host-seeking activity of Ixodes ricinus. These models are based on a 6-year whole-season monitoring of I. ricinus host-seeking activity on experimental fields in the Central Bohemia Region in a typical habitat, oakhornbeam forest, where tick-borne encephalitis (TBE) virus and Borrelia burgdorferi s.str., B. afzelii, and B. garinii have been found. Meteorological data provided by the CHMI meteorological station in Prague-Libus were used, and during the development of the forecasting algorithm micrometeorological data have been collected directly at the tick monitoring sites under selected synoptic weather situations. In the TICKPRO program, the two most successful models utilized ambient air temperature, quantity of atmospheric precipitation, and relative air humidity. The prediction determines 5 levels of risk of attack according to the current proportion of host-seeking ticks, and thus determines the risk of TBE infection. The levels of risk defined by the TICKPRO program are supplemented by instructions on how to prepare oneself for entering sites with potential tick occurrence, how to move around once there, and how to behave on returning home. This warning system is weekly published on websites of National Institute of Public Health and CHMI, Prague, over entire season (March-November).
Keywords: Ixodes; stromy; Seasons; Software; Trees; teoretické modely; hodnocení rizik; Models, Theoretical; software; klíště; Animals; lidé; Risk Assessment; Weather; roční období; počasí; Humans; zvířata